Malerba’s La scoperta dell’alfabeto - Francese, Joseph (Quaderni d'Italianistica)

(untitled) (Iter Press, 2022)
Luigi Malerba uses his knowledge of peasant society to publish, in 1963, his first book of fiction, La scoperta dell’alfabeto (The Discovery of the Alphabet). While this collection of brief narratives represents the sharecroppers known by Malerba in his youth, the focus of the text (and of this essay) is the narrating voice. Specifically, his transformation from “il ragazzo” (“the boy”) of the opening tale into “l’uomo” (the man) of the concluding novella. The tales of peasant life that comprise the bulk of the text are non-chronologically ordered elements of a recherche that, at the book’s end, leaves unelaborated and repressed the narrator’s participation in and perpetuation of the long-standing system of class oppression of which he is a beneficiary. Moreover, consideration of the modifications wrought in the definitive 1971 edition, when juxtaposed to the two experimental novels by Malerba published in the interim, Il serpent (The Serpent, 1966) and Salto morale (What Is This Buzzing? Do You Hear It Too?, 1968), enables us to chart Malerba’s gradual supersession of the neorealism of his mentor, Cesare Zavattini.